Our privacy: How to be assured in cyberspace - Zulhuda, Sonny (2016)
We have tonnes of confidential information digitised and stored in every possible storage media in cyberspace, via both popular applications, being direct cloud-based services and/or social media platform, and applications that are designed for a specific group of professionals. However, one question remains. What happens to the information after the click of the mouse? Can we forego privacy in return for convenience? Are we assured of our privacy from the one provider who is holding all the confidential information and our own business strategic plans? The panellists will share what it takes to protect privacy in the cyber world without losing the convenience.